Electroencephalographic abnormalities and imaging profile of neurocysticercosis: analysis of 60 cases in children - Saurabh, Kumar; Verma, Neelam; Ranjan, Shilpi (International Journal of Advances in Medicine, 2017)
Background: To study the electroencephalographic abnormalities and imaging profile of 60 children suffering from neurocysticercosis at a tertiary care centre over a period of two years. Methods: A diagnosis of Neurocysticercosis was made mainly on the basis of clinical features, imaging studies and serological tests. Patients were evaluated for different types of abnormalities on electroencephalogram (EEG) of their brains. This study group was subsequently evaluated for nature, type and site of lesion on computed tomographic scan and Magnetic Resonance Imaging of brain. Results: 28 (57.14%) cases had abnormal EEG finding in which nonspecific background changes was the commonest abnormalities. Solitary lesion (71.66%) were most common type of lesion. Parietal lobe was most common affected lobe followed by frontal lobe (18.6%). Transitional lesion (71.66%) in the form of ring enhancement following contrast administration was the prominent nature of lesion. Conclusions: Electroencephalographic abnormalities are not directly related to site and type of involvement. Parietal lobe was the most common affected lobe probably due to middle cerebral artery involvement.